The Application of Nationalist Character Values with Nationality in IPS Learning in SMP N 2 Kepil, Wonosobo District - Rani, Linda Lusi; Suyahmo, Suyahmo; Banowati, Eva (Universitas Negeri Semarang, 2018)
Social studies learning can develop the potential of students who can interpret the environment in schools, communities and countries, and become good citizens. This study is to analyze the application of nationalist-minded character values in social studies learning, and the success of the PPK program on nationalist values in social studies learning in class VII in the second semester of the 2017/2018 school year in SMP N 2 Kepil, Wonosobo District. The research uses qualitative methods. Data collection used are observation, interviews and documents. The researcher uses triangulation technique. Data analysis consists of three lines, namely: data reduction, data presentation, conclusion drawing or verification. The results of the study show that, the teacher prepares learning tools at the beginning of each semester and new school year. The teacher always exemplifies and reprimands the students. The teacher always integrates, incorporates and applies nationalist values that are nationalistic in the midst of learning activities with lectures, question and answer, and discussion. The students change in behavior that is better, although there are still some behaviors of students who lack of character. The implementation of the PPK program at school was not smooth, due to several factors, namely, sometimes the homeroom teacher did not monitor and supervise students in the class because there were tasks that had to be completed.The research hopes that students become good moral and achievement.